DO ORGANIZATIONAL TRUST AND PATERNALIST LEADERSHIP LEAD TO ORGANIZATIONAL IDENTIFICATION? (Third Sector Social Economic Review, 2021)
Although the positive results of organizational identification have been comprehensively discussed in the literature, the factors that can affect this concept have not been emphasized to the same extent. Therefore, in our research, it is aimed to examine the effects of two variables, such as paternalistic leadership and organizational trust, that can increase organizational identification. In addition, it is also investigated whether the tenure of the employees which affects behaviors of employees plays a moderator role in the relations between the mentioned variables. To achieve the purpose of the study, data were collected with quantitative methods from public organizations in Ankara. As a result of the analysis of the questionnaires applied to 232 employees, it has been revealed that the paternalistic leadership and organizational trust perceptions of the employees have positive effects on organizational identification. At the same time, it has been concluded that tenure has a moderating effect on these relations.
Keywords: Organizational Identification; Paternalist Leadership; Organizational Trust; Working Time; Moderating Effect